Persisting Gender Discrimination in Land Rights (Mussoorie, 2016)
India is an agraian society where 69% of its population lives in rural areas. Agricultural is the main source of livelihood for a large number of rural populations including women. Women constitute a major component of agricultural labor and contribute significantly to agricultural production yet they do not enjoy significant land ownership rights. Women?s lack of ownership of productive resources such as land weakens their bargaining capacity within the household as well as in the public sphere. This further excludes them from socio-political and legal institutions and they continue to be discriminated against. Studies have shown that the land and inheritance laws in most of the states in India are biased. Similar situation may be seen in north eastern states where customary laws are in practice. There is a great need to revisit the land laws in order to remove the existing anomalies.
Keywords: Social Group